2020
DOI: 10.1111/jace.17452
|View full text |Cite
|
Sign up to set email alerts
|

Unique performance of thermal barrier coatings made of yttria‐stabilized zirconia at extreme temperatures (>1500°C)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Therefore, vertical crack propagation is promoted by thermal shock. This is consistent with the experimental observation that fast cooling leads to reduced TBC lifetime during thermal cycling in burner rig tests 18 . It is worth noting that the SIF scales with the coating's Young's modulus.…”
Section: Coupled Effect Of Sintering and Thermal Cyclingsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, vertical crack propagation is promoted by thermal shock. This is consistent with the experimental observation that fast cooling leads to reduced TBC lifetime during thermal cycling in burner rig tests 18 . It is worth noting that the SIF scales with the coating's Young's modulus.…”
Section: Coupled Effect Of Sintering and Thermal Cyclingsupporting
confidence: 89%
“…In the sintering test and real service condition, faster cooling is expected at the coating surface as the engine shuts down (i.e., a thermal shock condition 15, 17, 18 ). The effect of this on the SIF is examined by introducing an intermediate state.…”
Section: Coupled Effect Of Sintering and Thermal Cyclingmentioning
confidence: 99%
“…Figure 4 (a) shows photographs of a military helicopter operating in a desert environment, leading to the engine components covered with the re-solidified CMAS sand, and the resulting damage (Fig. 4 b) (Ref 21 , 22 ).
Fig.
…”
Section: Technologymentioning
confidence: 99%
“…Vaben et al used custom-made burner rig to simulate TBC in thermal cyclic condition at 1500 • C, which was equipped with 1050 • C cooling air to determine the effects of transient cooling [58]. Transient cooling during the high temperature exposure of TBC will accelerate the failure.…”
Section: Thermal Cyclic Test Rigmentioning
confidence: 99%
“…TBC was tested under cyclic conditions either by using a custom-made test rig that was equipped with the cooling air system [58][59][60][61]65], that was not equipped with the cooling air system [68], or a commercial test rig that was not equipped with the cooling air system [62,64]. These showed that there are a number of studies have developed test rigs that are capable of simulating TBC-assisted cooling air system.…”
Section: Thermal Cyclic Test Rigmentioning
confidence: 99%